KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN MINAT BELAJAR SISWA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION BERBANTUAN ARTIFICIAL INTELEGENCE - Nurhayani, Sindi; Cahyani, Rianti; Saefuloh, Nandang Arif (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
Abstract This research is based on the fact of low concept understanding ability and learning interest of students at school. This study aims to find out whether the learning approach of Realistic Mathmetics Education and animated videos assisted by artificial intelligence can improve students' ability to understand concepts and learning interests. This research is a qualitative research with the Classroom Action Research (PTK) method which consists of two cycles. The subject of this study is students in grades VII-8 of SMP Negeri 51 Bandung consisting of 34 students. Data was obtained from tests, observations, questionnaires, and field notes. The results of the concept comprehension ability test were analyzed using the average ability and percentage of learning completion. The results of the learning interest questionnaire and student responses were analyzed using the Likert scale. Based on the analysis of the data obtained, it can be concluded that students' understanding of mathematical concepts increases, students' interest in learning increases, and students' response to learning with the Realistic Mathematics Education approach and artificial intelligence-assisted animation videos is positive.